Valuing And Characterization of Smallholder’s Forest In West Java - Hernawan, Endang; Lastini, Tien; Rosmiati, Mia (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2024)
Today, smallholder forests in West Java - Indonesia play an important role as suppliers of domestic and industrial wood needs. However, with forest managers who are not yet professional and the easy conversion of land use into non-forest, smallholder forests cannot guarantee the sustainability of wood supply. In supporting the implementation of sustainable forest management in smallholder forests, understanding is needed regarding the characteristics of smallholder forests. The purpose of this study is to evaluate the characteristics of smallholder forest stands as a basis for assessing the sustainability of wood raw material supply. The research location is smallholder forest in Sumedang district. Data collection method is a purposive sampling method with moving plot. The results indicated that the density of smallholder forests per ha was 342.5 trees per ha, with 14 species of trees. The distribution of tree diameters ranges from 1-49 cm, with a predominant class diameter of 10-15 cm. The potential stands for smallholder forests are 32.68 m3ha-1. The cutting felling cycle is at the age of 6.5 years with a selective logging system at a diameter size of more than 15 cm, so it is not optimal and there is a tendency that it will not continue. Therefore, in increasing its sustainability, it is necessary to increase the cutting life. So, there is a tendency for community forest areas to be converted into other land uses.